The Effect Of Rewards and Competence On Employee Performance with Punishment as an Intervening Variable in West Sumatra Regional Office of BPJS Ketenagakerjaan - Age Hidayat; Kiki Farida Ferine; M. Isa Indrawan (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study aims to analyze the effect of reward and competence on employee performance , with punishment as an intervening variable at West Sumatra Regional Office of BPJS Ketenagakerjaan.This research employs a quantitative approach using a survey method. The population consists of all employees of West Sumatra Regional Office of BPJS Ketenagakerjaan, with a total sample of 109 employees , selected using a census sampling technique . Data were collected through questionnaires and analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS software. The results indicate that reward and competence have a positive and significant effect on employee performance . Furthermore, reward and competence also have a positive and significant effect on punishment , and punishment has a positive and significant effect on employee performance . The indirect effect analysis shows that punishment mediates the relationship between reward and competence and employee performance . Therefore, it can be concluded that improving employee performance can be achieved through appropriate reward systems, enhanced employee competence, and the effective and proportional implementation of punishment.